T-Cell Subsets in Rheumatoid Arthritis Patients on Long-Term Anti-TNF or IL-6 Receptor Blocker Therapy - Dulic, Sonja; Vásárhelyi, Zsófia; Sava, Florentina; Berta, László; Szalay, Balázs; Toldi, Gergely; Kovács, László; Balog, Attila (Mediators of Inflammation, 2017)
Data on the impact of biological therapies on the T-cell phenotype in rheumatoid arthritis are limited. Here, we prospectively measured the percentages of 15 circulating T-cell subtypes using flow cytometry. We obtained transversal and longitudinal data in 30 anti-TNF responders, 19 secondary anti-TNF nonresponders, and 43 IL-6R antagonist responders, before, 8 weeks and at least 6 months after biological therapy. Untreated RA patients and healthy controls were also included. The important findings are the following: (1) the proportion of regulatory T-cells (Tregs) which are decreased in untreated RA patients becomes normal in all long-term-treated groups; (2) in anti-TNF responders as well as in nonresponders, the frequencies of naïve CD4+ and CD8+ cells are lower, whereas those of proinflammatory Th1, Th2, and Th17 cells and HLA-DR+-activated cells are higher than those in untreated RA or healthy controls; (3) in IL-6R responders, Th1 proportion is decreased, while that of Th2 and Th17 is increased as compared to that in anti-TNF-treated patients and controls; (4) pending confirmation, a CD4CD69 ratio < 2.43 at baseline, could be useful to predict a good therapeutic response to anti-TNF therapy. This study provides comprehensive information regarding the long-term impacts of those biological therapies on the ecotaxis of T-cells in RA. The ClinicalTrials.gov registration number of our study is NCT03266822.